Value networks in manufacturing : sustainability and performance excellence - Liyanage, Jayantha P.; Uusitalo, Teuvo (Springer, 2016)
This book highlights innovative solutions together with various techniques and methods that can help support the manufacturing sector to excel in economic, social, and environmental terms in networked business environments. The book also furthers understanding of sustainable manufacturing from the perspective of value creation in manufacturing networks, by capitalizing on the outcomes of the European 'Sustainable Value Creation in Manufacturing Networks' project. New dynamics and uncertainties in modern markets call for innovative solutions in the global manufacturing sector. While the manufacturing sector is traditionally driven by technology, it also requires other managerial and organizational solutions in terms of network governance, business models, sustainable solution development for products and services, performance management portals, etc., which can provide major competitive advantages for companies. At the same time, the manufacturing industry is subject to a change process, where business networks play a major role in value-creating processes. By far the biggest challenge in this context is making value creation a sustainable process where economic, social, and environmental demands are met. Managing product and service-related business operations in manufacturing networks thus brings different challenges that cannot purely be resolved using traditional methods, and techniques. This book is an outcome of a European project funded by the European Commission, and performed by a dedicated R & D consortium comprised of some leading Research institutions and Industrial partners.- Resumé vydavatel
Keywords: výrobní management -- environmentální aspekty; udržitelný rozvoj; production management -- environmental aspects; sustainable development; elektronické knihy; sborníky; electronic books; papers of several authors